The first phased-array antennas in Russia 1955-1960. - Vendik, Orest G. (IEEE Antennas & propagation magazine.)
The first phased-array antenna in the Soviet Union was developed under the supervision of Professor Yuri Yurov, at Leningrad Electrical Engineering Institute (Technical University), in 1955. It was a four-element array of dielectric-rod radiators, fed through reciprocal ferrite phase shifters. The array was intended for use in radar, for automatic aiming at the target. In Yurov's group, the theory of phased-array antennas was developed. In 1960, a 61-element array, in the form of a lens filled with ferrite phase shifters, was designed, manufactured, and investigated. Later, the investigations were moved from the university to industrial research centers.